2005
DOI: 10.4319/lo.2005.50.1.0217
|View full text |Cite
|
Sign up to set email alerts
|

Responses in dissolved nutrients and epilithon abundance to spawning salmon in southeast Alaska streams

Abstract: Spawning Pacific salmon (Oncorhynchus spp.) historically transported massive quantities of marine-derived nutrients (MDN) into nutrient-poor streams of the Pacific Northwest. In southeast Alaska, we measured the effects of MDN on streamwater chemistry and epilithon standing stock (1) through time during two consecutive years in one stream, Fish Creek; (2) over space in six salmon streams; and (3) salmon carcasses in artificial streams. Overall, salmon clearly increased the concentrations of important dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 35 publications
9
105
2
Order By: Relevance
“…Previous studies tracking dissolved nutrients have shown similar patterns (Minakawa and Gara 1999, Chaloner et al 2002, Johnston et al 2004, Mitchell and Lamberti 2005, Claeson et al 2006. Delta 15 N in horsetail and scraper macroinvertebrates did not vary with spawner density in any season, suggesting little or no MDN assimilation by these lower trophic levels.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies tracking dissolved nutrients have shown similar patterns (Minakawa and Gara 1999, Chaloner et al 2002, Johnston et al 2004, Mitchell and Lamberti 2005, Claeson et al 2006. Delta 15 N in horsetail and scraper macroinvertebrates did not vary with spawner density in any season, suggesting little or no MDN assimilation by these lower trophic levels.…”
Section: Discussionmentioning
confidence: 54%
“…The upstream site (Upper Peterson) is above a barrier waterfall that blocks spawning salmon, whereas the downstream site (Lower Peterson) receives spawning runs of Oncorhynchus gorbushcha (pink salmon), Oncorhynchus keta (chum salmon), and Onchorhynchus kisutch (coho salmon) in the late summer and autumn (JulySeptember). The maximum wet mass of the Peterson Creek salmon run has been estimated at .200,000 kg (Bethers et al 1993) and previously measured spawner densities range from 0 to 0.53 fish m 22 (Mitchell and Lamberti 2005). During this study, salmon were first observed at the site on the 02 August sampling date and the majority of carcasses were washed downstream from the site by 03 September.…”
Section: Methodsmentioning
confidence: 73%
“…In studies in Peterson Creek (Chaloner et al 2004;Mitchell and Lamberti 2005) and in other streams in Alaska, Canada, and the Great Lakes (Sugai and Burrell 1984;Schuldt and Hershey 1995;Minakawa and Gara 1999;Johnston et al 2004; R. T. Edwards unpubl. data), streamwater concentrations of NH 4 -N associated with salmon spawning did not exceed 300 mg L 21 and concentrations of SRP did not exceed 40 mg L 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the net effects of spawning salmon can vary (Harding et al 2014); salmon can subsidize freshwater and riparian habitats through excretion and egg and carcass deposition (Kline et al 1990, Cederholm et al 1999, Janetski et al 2009, and can export nutrients with juvenile emigration and disturbance as adults dig and defend nests (Moore et al 2007, Kohler et al 2013. Although considerable amounts of salmon-derived nutrients imported into coastal watersheds are retained, large proportions are also exported downstream to estuaries (Gende et al 2004, Mitchell and Lamberti 2005, Cak et al 2008. The influence of salmon nutrients in estuaries has received some mention (Reimchen 1994, Wipfli et al 1998, Cederholm et al 1999, Lessard and Merritt 2006, Field and Reynolds 2013, but research on the topic is limited (Fujiwara and Highsmith 1997, Jauquet et al 2003, Cak et al 2008.…”
Section: Introductionmentioning
confidence: 99%